Agronomic behavior grafts of watermelon in Puerto Cayo in Ecuador - Gabriel-Ortega, Julio (2023)
Introduction. Water melon (Citrullus lanatus L.) is an important crop in Puerto la Boca area, this area requires the development of new technological alternatives such as grafts to counteract pest problems (aphids, thrips and whitefly) and diseases such as mildew velloso (Pseudoperonospora cubensis). Objective. Evaluate the agronomic behavior of grafted watermelon plants and their profitability. Materials and methods. The tests were implemented in the field in an experimental design of completely random blocks, where 10 treatments and 10 repetitions were applied. The treatments resulted from the combination of 4 patrons of zapallo, 2 grafted watermelon and the control. The patrons were: P1: alamama, P2: zapallo manabita, P3: zapallo verde and P4: zapallo guitarrilla grande. The injections were: I1: sandia quetzali and I2: sandia charleston gray and the control were the last materials. The response variables where plant height, stem diameter, number of branches, number of guides, number of internodes, percentage of severity of mildiu octopus, number of flowers, number of fruit sets, number of fruits, volume of fruit and weight of fruits. Afterwards, the core refactoring index, percentage of total solids and temperature were evaluated. A benefit/ cost analysis of the treatments was carried out through partial assumptions. Results. There was a 91.06% germination of seed of zapallo and watermelon varieties. 798 grafted plants were transplanted 83.13%. The highest profitability (benefit/cost) of the fruits was US $3.80 at the supermarket and US $1.90 at the Jipijapa supply market. Conclusion. There was a high germination of seeds of the varieties of zapallo and watermelon, obtaining enough plants for field transplantation. The grafting between quetzali and zapallo verde, showed vigor and sanity similar to the control quetzali.